Applications of Protein Microarrays in Biomarker Discovery for Autoimmune Diseases - Li, Siting; Song, Guang; Bai, Yina; Song, Ning; Zhao, Jiuliang; Liu, Jian; Hu, Chaojun (Frontiers in Immunology, 2021)
Dysregulated autoantibodies and cytokines were deemed to provide important cues for potential illnesses, such as various carcinomas and autoimmune diseases. More and more biotechnological approaches have been applied to screen and identify the specific alterations of these biomolecules as distinctive biomarkers in diseases, especially autoimmune diseases. As a versatile and robust platform, protein microarray technology allows researchers to easily profile dysregulated autoantibodies and cytokines associated with autoimmune diseases using various biological specimens, mainly serum samples. Here, we summarize the applications of protein microarrays in biomarker discovery for autoimmune diseases. In addition, the key issues in the process of using this approach are presented for improving future studies.